Exploring alternative materials for bamboo panel walls in the conservation of the Ihsaniah Iskandariah Mosque: a concept paper / Syed Abdul Haris Syed Mustapa ... [et al.] - Syed Mustapa, Syed Abdul Haris; Wan Mohd Azmi, Wan Faida; Ab Wahab, Lilawati; Baharuddin, Mohd Nurfaisal; Musa, Muhammad Suhaimi (Universiti Teknologi MARA, Perak, 2024)
The lhsaniah Iskandariah Mosque, Kuala Dal, Perak, serves as a symbol of Malaysia's cultural identity, making its preservation crucial for future generations. Despite previous conservation efforts, sections of the mosque's bamboo panel walls have suffered deterioration. The climate and environmental conditions in Malaysia, including high humidity and rainfall, pose challenges to the longevity of traditional materials like bamboo. To address this challenge, there is a need to explore alternative materials that offer enhanced durability, weather resistance, and sustainability. Researching alternative materials represents a proactive step towards preserving our cultural heritage. It not only fortifies the structural integrity of iconic landmarks like the Ihsaniah Iskandariah Mosque but also mitigates the environmental footprint of conservation efforts. Moreover, this endeavour catalyses adaptation strategies for climate change, propelling us toward a future where heritage conservation seamlessly aligns with sustainable development goals. This paper emphasizes the importance of collaborative research efforts in developing innovative solutions for conservation, ultimately safeguarding Malaysia's cultural heritage for future generations and promoting cultural tourism. Research on these alternative materials needs to be conducted, and the findings will assist the National Heritage Department in making decisions regarding the replacement of the mosque's bamboo panel walls.